Experimental Algorithms 12th International Symposium, SEA 2013, Rome, Italy, June 5-7, 2013. Proceedings - Bonifaci, Vincenzo.; Demetrescu, Camil.; Marchetti-Spaccamela, Alberto. (Lecture Notes in Computer Science,, 2013)
This book constitutes the refereed proceedings of the 12th International Symposium on Experimental Algorithms, SEA 2013, held in Rome, Italy, in June 2013. The 32 revised full papers presented together with 3 invited papers were carefully reviewed and selected from 73 submissions. The papers are organized in topical sections on transportation networks and graph algorithms, combinatorics and enumeration, data structures and compression, network partitioning and bioinformatics, mathematical programming, geometry and optimization, and scheduling and local search.